ANALISIS DIKSI DALAM BERITA KRIMINAL PEREMPUAN PADA MEDIA ONLINE POSMETRO PADANG EDISI JUNI DAN JULI 2025 - Selvia Agustin; Wahyudi Rahmat; Iswadi Bahardur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The choice of diction in mass media reporting, especially crime news involving women as victims or perpetrators is the reason for this research. Diction not only functions to convey information, but also forms the construction of reality and influences the reader's perspective on an event. This study aims to describe the types of diction used in women's crime news in the online media Posmetro Padang June and July 2025 editions, as well as to analyze the denotative and connotative meanings of the diction. The type of research used is descriptive qualitative with the listening and note-taking method. The research data are in the form of excerpts from women's crime news published in the online media Posmetro Padang. Data analysis was carried out using the referential matching method and the distribution method through the replace, disappear, and read markah techniques. Based on the results of the data analysis, it shows that women's crime news in the online media Posmetro Padang uses a lot of connotative diction, such as molest, raped, and sex slave, which creates an emotional impression and frames women as vulnerable and marginalized parties. Denotative diction such as the words molestation and rape. The choice of connotative diction is more dominant because it serves to create a dramatic effect and attract the reader's attention. However, on the other hand, it can reinforce gender stereotypes towards women.